KETERGANTUNGAN BEBERAPA SEKTOR INDUSTRI TERHADAP BAHAN BAKU IMPOR - Reni Kristina Arianti (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2008)
Manufacturing industry sector changes by structural transformation from industry-based on import substitution to export-oriented industry. Anticipating the rise of imports, especially the increasing of raw material, the Government needs to encourage the growth of the national industry, especially the development of raw material industries in the country as a source of job creation and a source of foreign exchange and national economic value added. This high importation because the resources are not available in this country; a local source of raw materials and quality standards not yet adequate and has not been in accordance with the request of lower domestic industry; when avalaible in this country predicted to be more expensive; hard to get or there is no existence of supply continuity. To find out the level of dependency of national industry to imported raw material, this research uses regression analysis tool with three equations, those are equations output, equation of value added and income equality. Beside of secondary data analysis, this research also conducted a survey to know the perception of businessmen/exporters which are employers see the import dependence and the possibility of imports substitution, especially imports of raw material with domestic raw materials. Based on the result of analysis, it may be known that the elasticity of the imported raw material is higher than domestic raw material for some sectors such as: footwear sector, electronic chemical sector, also vehicle and its components sector. Some sectors have been rational in using domestic and imported raw material, that is sector with higher elasticity of imported raw material than domestic raw material, such as footwear and electronic. But there are some sectors that are not rational in deciding proportion of imported raw material, although elesticity of imported raw materials higher than domestic raw materials, proportion of imported raw material smaller than domestic raw material, such as chemical sector as well as the vehicle and its component sector.